PERAN MANAJEMEN SARANA PRASARANA DAN IKLIM PESANTREN DALAM MENINGKATKAN MUTU LAYANAN PENDIDIKAN (PENELITIAN DI PESANTREN MIFTAHUL ULUM GANDOK) - Ajeng Distyani Eka Wibowo; Rosid Bahar; Asep Deni (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the influence of infrastructure management and pesantren climate on the quality of educational services at Pondok Pesantren Miftahul Ulum Gandok, both partially and simultaneously. This study employed a quantitative approach with a correlational design. The population consisted of all final-year students in the 2025/2026 academic year, with the sample determined using the Slovin formula and purposive sampling technique. The instrument was a 5-point Likert scale questionnaire comprising 36 items, validated using Product Moment Pearson (r ≥ 0.2144) and reliability tested via Cronbach’s Alpha (α = 0.920). Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) through IBM SPSS 25. Infrastructure management had a positive and significant effect on educational service quality (β = 0.302; t = 2.225; p = 0.030). Pesantren climate also showed a positive and significant effect (β = 0.436; t = 3.217; p = 0.002), with a greater contribution than infrastructure management. Simultaneously, both variables significantly influenced educational service quality (F = 24.884; p = 0.000), jointly explaining 46.6% of the variance (R² = 0.466). This study reveals that the socio-psychological climate of pesantren has stronger predictive power over educational service quality than physical infrastructure, offering a new perspective in integrated quality improvement strategies for Islamic boarding school institutions.